Theoretical Studies of the Structure of the Metal-carbon Composites on the Base of Acryle-nitrile Nanopolimer - I.V. Zaporotskova; N.A. Anikeev; L.V. Kojitov; O.A. Davletova; A.V. Popkova (Журнал нано- та електронної фізики)
The presence of the metal compounds in the acryle-nitrile nanopolimer (PPAN) leads to the formation of the metal nanoparticles. The metal-carbon nanocomposites based on PPAN including pair connections with iron and cobalt has been theoretically investigated. The spatial configuration of the nanocomposite for each option of the arrangement of metal atoms has been received. The analysis of the received results for all options of the arrangement of the metal atoms allowed defining the binding energy of the systems and the width of the forbidden gap ΔЕg of the nanocomposite. The analysis of the electronic and energy structures of the system found out that the introduction of the metal atoms leaded to the essential reduction of the width of the forbidden zone of the composite in comparison with the pure PPAN.